Using the Brain as a Metaphor to Model Flexible Production Systems - Garud, Raghu; Kotha, Suresh (Academy of Management Review, 1994)
Manufacturing flexibility is critical for survival in industries characterized by rapid change and diverse product markets. Although new manufacturing technologies make it possible to accomplish flexibility, their potential remains unrealized by firms whose organizational elements do not possess adaptive capabilities. We use the brain as a metaphor to generate insights on how firms might design flexible production systems. We chose the brain as a metaphor because it is a self-organizing system capable of responding rapidly to a broad range of external stimuli. The brain as a metaphor suggests that flexibility can be enhanced by employing practices that promote distributed processes occurring in parallel manner. Such practices lie in contrast to those employed by production systems built on scientific management principles that promote localized processes in a sequential manner. By exploring these contrasting modes of operation, we argue that the brain as a metaphor opens up new avenues for theory development related to the design of flexible production systems.